(untitled) (Applied Biological Research, 2024)
The synthesis and characterization of various nanoparticles using the extracts from Hibiscus ficulneus L., a medicinal plant known for its therapeutic properties, were investigated. Nanoparticles of three metals, namely silver, copper and zinc (used in the form of silver nitrate, copper sulphate, and zinc sulphate) were synthesized. The presence of nanoparticles was confirmed by observing a spectrum in visible range, which was carried out using a UV-visible spectrophotometer. To observe the crystalline structure, XRD analysis was performed. SEM analysis revealed uniformly distributed silver nanoparticles on the surfaces of the cells. The silver nanoparticles were spherical in shape with particle size in the range of 2 to 20 μm. The antimicrobial activity of the synthesized nanoparticles was evaluated using the zone of inhibition method. The highest antimicrobial activity was observed with silver nanoparticles as compared to the other silver nano particle extracts, particularly against Pseudomonas aeruginosa (20 mm). These results highlight the significant antimicrobial potential of silver nanoparticles against pathogenic bacteria. This study underscores the role of terrestrial products as potential sources for pharmaceutical applications.